2015
DOI: 10.3171/2015.3.focus1535
|View full text |Cite
|
Sign up to set email alerts
|

Neurostimulation to improve level of consciousness in patients with epilepsy

Abstract: When drug-resistant epilepsy is poorly localized or surgical resection is contraindicated, current neurostimulation strategies such as deep brain stimulation and vagal nerve stimulation can palliate the frequency or severity of seizures. However, despite medical and neuromodulatory therapy, a significant proportion of patients continue to experience disabling seizures that impair awareness, causing disability and risking injury or sudden unexplained death. We propose a novel strategy in which neuromodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 105 publications
2
25
0
Order By: Relevance
“…We cannot imagine a situation where the ascending endogenous neuromodulatory pathways carrying sensory information via cranial nerves do not contribute a significant degree to the observations made using tDCS and some other tES methods. Our studies as well as the studies of many others [16,18,23,32,33,39,62,63,[68][69][70][71][72][73][74][75][76][77] on electrical neuromodulation or stimulation of cranial nerves indicate that investigators applying electrical currents (DC, AC, or other) to the skin of the head should consider the impact of bottom-up pathways as illustrated in Figure 7. The possible involvement of bottom-up pathways has been almost entirely overlooked by the scientific community that implements tES.…”
Section: Potential Implications For the Field Noninvasive Brain Stimumentioning
confidence: 67%
See 1 more Smart Citation
“…We cannot imagine a situation where the ascending endogenous neuromodulatory pathways carrying sensory information via cranial nerves do not contribute a significant degree to the observations made using tDCS and some other tES methods. Our studies as well as the studies of many others [16,18,23,32,33,39,62,63,[68][69][70][71][72][73][74][75][76][77] on electrical neuromodulation or stimulation of cranial nerves indicate that investigators applying electrical currents (DC, AC, or other) to the skin of the head should consider the impact of bottom-up pathways as illustrated in Figure 7. The possible involvement of bottom-up pathways has been almost entirely overlooked by the scientific community that implements tES.…”
Section: Potential Implications For the Field Noninvasive Brain Stimumentioning
confidence: 67%
“…Depending on their firing rates for example, neurons of the PPN can differentially mediate REM sleep states [1,12] and neurons of the LC can trigger sleep/wake transitions [13,14]. Disrupted activity of ascending RAS networks underlies several neuropsychiatric conditions and disorders, such as insomnia, anxiety, depression, posttraumatic stress disorder (PTSD), and attention deficit hyperactivity disorder (ADHD) [1,[15][16][17]. Therefore, a neural interface capable of dynamically and electrically modulating RAS networks should be able to provide a chemical-free approach to restoring poor daily function attributable to sleep loss or attention and mood disorders.…”
Section: Introductionmentioning
confidence: 99%
“…CL, central lateral; RAS, reticular activating system; SNR, substantia nigra pars reticulate; SC, superior colliculus; LC, locus coeruleus; IPL, inferior parietal lobule; ANT, anterior nucleus of thalamus; DBS, deep brain stimulation; mPFC, medial prefrontal cortex; LO, lateral orbitofrontal cortex; TMN, tuberomammillary nucleus; VTA, ventral tegmental area; MCS, minimally conscious state; CM-Pf, centromedian–parafasciular nucleus; NA, nucleus accumbens; NTS, nucleus tractus solitarius; VS, vegetative state. This figure is adapted with permission from Gummadavelli et al (2015a) .…”
Section: Neuromodulation Of the Seizure Networkmentioning
confidence: 99%
“…Studies in rodent models of temporal lobe epilepsy have suggested that neurostimulation in the intralaminar thalamus is capable of reversing the commonly noted post-ictal cortical slow waves ( Gummadavelli et al, 2015b ) and may participate in the reversal of widespread cortical slow waves seen during temporal seizures. Neuromodulation of intralaminar thalamic nuclei and other nuclei of the ascending arousal system during seizures to restore consciousness remains under active investigation at our center ( Gummadavelli et al, 2015a , b ; Motelow et al, 2015 ; Kundishora et al, 2017 ).…”
Section: Neuromodulation Of the Seizure Networkmentioning
confidence: 99%
“…Various neural targets have been investigated in numerous clinical and animal studies involving the cerebellum, brain stem, reticular activating system, hypothalamus, thalamic basal ganglia, basal forebrain, limbic system, and so on. The feasibility, benefits, and pitfalls of such therapy vary with the targets of DBS [ 201 - 204 ]. One study reported that epilepsy patients undergoing DBS directed to the anterior nuclear thalami experienced significantly more electroclinical arousals during the stimulation periods.…”
Section: Sleep and Anticonvulsant Therapymentioning
confidence: 99%